MANFAAT PEMBIAYAAN PRODUKTIF TERHADAP PENINGKATAN KESEJAHTERAAN ANGGOTA KSPPS BMT BERKAH MADANI - Evi Ayu Wandini; Stevani Adinda Nurul Huda (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2024)
Microfinance institutions called Sharia cooperatives utilize the economic resources of their members to achieve their objectives. Law Number 25 of 1992 article 3 which contains the objectives of the cooperative includes the following three things; (1) To improve the welfare of its members; (2) To improve the welfare of the community; (3) To play an active role in the national economic order. The objective of this research is to assess if the welfare of members of KSPPS BMT Berkah Madani who are Micro, Small and Medium Enterprises (MSMEs) has been improved after financing. This research uses a qualitative approach with descriptive writing techniques with triangulation techniques in collecting data through interviews, observation and documentation. The results of this study indicate that the implementation of the financing program at KSPPS BMT Berkah Madani has an effect on improving the welfare of two Micro, Small and Medium Enterprises (MSMEs) of its members, even to expand and develop their business, and create new jobs.